Resiliensi dan Partisipasi Generasi “Z” Dalam Mendukung Misi GPdI di Jemaat Elohim Sentani-Jayapura - Gainau, Markus S.; Pandi, Seprianti E. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Generation Z (Gen Z) are adolescents known for multitasking, high technological adaptability, creativity, and curiosity. This study explores the integration of Christian Religious Education (PAK) in fostering resilience and effective participation of Gen Z at GPdI Elohim Sentani in facing global challenges. This study focuses on the role and relevance of PAK in strengthening resilience (relevance, active learning, technology) and participation (service, mentorship, community connection). This study used qualitative descriptive method with thematic analysis. Data were collected through questionnaires from 30 church adolescents and Focus Group Discussions (FGD) included interview. The questionnaire data were analyzed with Likert and Guttman scales to measure resilience and participation. Interviews were processed with reduction and indexing techniques. The results show that Gen Z at GPdI Elohim Sentani has a strong understanding of the importance of Christian teachings, with a 100% response rate. However, only 33.33% engaged in active learning, and 83.33% rated the role of technology very positively. Participation in church service and mentorship was low at 33.33%. Nevertheless, community connection among congregants was positive, with 43.33% having very good relationships and 57.67% good relationships. Low participation of Gen Z at GPdI Elohim is caused by the relevance of interest.